The DNA damage response promotes polyomavirus JC infection by nucleus to cytoplasm NF- kappaB activation - White, Martyn K. (Virol J, 2017)
BACKGROUND: Infection of glial cells by human neurotropic polyomavirus JC (JCV), the causative agent of the CNS demyelinating disease progressive multifocal leukoencephalopathy (PML), rapidly inflicts damage to cellular DNA. This activates DNA damage response (DDR) signaling including induction of expression of DNA repair factor Rad51. We previously reported that Rad51 co-operates with the transcription factor NF-κB p65 to activate JCV early transcription. Thus Rad51 induction by JCV infection may provide positive feedback for viral activation early in JCV infection. DDR is also known to stimulate NF-κB activity, a phenomenon known as nucleus to cytoplasm or “inside-out” NF-κB signaling, which is initiated by Ataxia telangiectasia mutated (ATM) protein, a serine/threonine kinase recruited and activated by DNA double-strand breaks. Downstream of ATM, there occurs a series of post-translational modifications of NF-κB essential modulator (NEMO), the γ regulatory subunit of inhibitor of NF-κB (IκB) kinase (IKK), resulting in NF-κB activation. METHODS: We analyzed the effects of downstream pathways in the DDR by phosphospecific Western blots and analysis of the subcellular distribution of NEMO by cell fractionation and immunocytochemistry. The role of DDR in JCV infection was analyzed using a small molecule inhibitor of ATM (KU-55933). NEMO sumoylation was investigated by Western and association of ATM and NEMO by immunoprecipitation/Western blots. RESULTS: We show that JCV infection caused phosphorylation and activation of ATM while KU-55933 inhibited JCV replication. JCV infection caused a redistribution of NEMO from cytoplasm to nucleus. Co-expression of JCV large T-antigen and FLAG-tagged NEMO showed the occurrence of sumoylation of NEMO, while co-expression of ATM and FLAG-NEMO demonstrated physical association between ATM and NEMO. CONCLUSIONS: We propose a model where JCV infection induces both overexpression of Rad51 protein and activation of the nucleus to cytoplasm NF-κB signaling pathway, which then act together to enhance JCV gene expression.